2022
DOI: 10.4236/gep.2022.1012004
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Geochemistry and Saltwater Intrusion in the Dakar Coastal Area, Senegal

Abstract: Groundwater levels and water samples were collected from 20 drinking water pumping and piezometer wells in the urban area of Dakar coastal region in the year 2019. The pH-value, electrical conductivity, as well as calcium, magnesium, sodium, potassium, chloride, sulfate, bicarbonate, and nitrate concentrations were measured to assess the hydrochemical quality of the infrabasaltic aquifer in the area. The present work carried out a hydrochemical analysis to interpret the groundwater chemistry of the aquifer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Other research reports that the Turc method has historically performed well under humid (Jensen et al, 1990;Trajkovic and Kolakovic, 2009b;Fisher & Pringle, 2013;Birara et al, 2020) and tropic conditions (Tukimat et al, 2012;Lima et al, 2019;Santos et al, 2019;Monteiro et al, 2021). One of the possible reasons is that the method was initially developed under wet conditions (southern France) (Tabari, 2010;Ahmadi and Javanbakht 2020;Diouf et al, 2016). In a semiarid region in Senegal Diouf et al (2016) concluded that the Turc method showed similar high accuracy (R2>0.80) reported in this research.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Other research reports that the Turc method has historically performed well under humid (Jensen et al, 1990;Trajkovic and Kolakovic, 2009b;Fisher & Pringle, 2013;Birara et al, 2020) and tropic conditions (Tukimat et al, 2012;Lima et al, 2019;Santos et al, 2019;Monteiro et al, 2021). One of the possible reasons is that the method was initially developed under wet conditions (southern France) (Tabari, 2010;Ahmadi and Javanbakht 2020;Diouf et al, 2016). In a semiarid region in Senegal Diouf et al (2016) concluded that the Turc method showed similar high accuracy (R2>0.80) reported in this research.…”
Section: Resultssupporting
confidence: 54%
“…One of the possible reasons is that the method was initially developed under wet conditions (southern France) (Tabari, 2010;Ahmadi and Javanbakht 2020;Diouf et al, 2016). In a semiarid region in Senegal Diouf et al (2016) concluded that the Turc method showed similar high accuracy (R2>0.80) reported in this research. Similar findings were observed in Malaysia, where Goh et al (2021) concluded that the Turc method provides the closest results to FAO-PM56 in subhumid and humid climate conditions in the absence of data, as the R2 and the MBE reported one of the 2019) concluded that the best option when meteorological data is unavailable is the Turc method given the R results (0.90) concerning FAO-PM56.…”
Section: Resultssupporting
confidence: 54%
“…In this study, in addition to other hydrochemical ratios, the Simpson coefficient Cl − /(HCO 3 − + CO 3 2+ ) was used, too. Five classes of groundwater are distinguished in function of this coefficient; good quality (<0.5), slightly contaminated (0.5-1.3), moderately contaminated (1.3-2.8), injuriously contaminated (2.6-6.6) and highly contaminated (6.6-15.5) [28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…The r (Na + /Cl − ) ratio combined with the other considered hydrochemical parameters, may indicate the origin of the ions in groundwater, even when the Cl − ion content is rather low. The ratio r(Na + /Cl − ) < 1 is an indicator of the seawater intrusion, while r(Na + /Cl − ) > 1 indicates an anthropogenic pollution [30][31][32]. When r(Ca 2+ /Mg 2+ ) < 1, the predominance of Mg 2+ over the Ca 2+ ion content can be attributed to the seawater's intrusion [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation